PEMBARUAN HUKUM KELUARGA: WASIAT UNTUK AHLI WARIS (Studi Komparatif Tunisia, Syria, Mesir dan Indonesia) - Abubakar, Fatum (Hunafa: Jurnal Studia Islamika, 2011)
The Islamic  law of inhreritance serves as one of the objects discussed in  studies of  Islamic law. However, the implementation of  the Islamic  law in the field of  inheritance  is not neccerally the same as that implemented in  Muslim countires. The Muslim countries such as Tunis, Syria, Egypt and Indonesaia implement the Islamic law of  inheritance but they do not possess the same understanding on the implementation of Islamic law of inheritance. The differencies lay on whoever elegible to receive the the property left by the dead persons and how many of the properties can be inherited; and whoever have the right to accept the inheritance from the dead person are among the questions discussed in this article in the respect of  the implemenatiuon of Islamic law of inheritance in the four Muslim Countries.